Relationship of differences in immunoglobulin heavy/light chain pairs (Hevylite), selected laboratory parameters and stratification systems in different immunochemical types of multiple myeloma - Scudla, Vlastimil; Lochman, Pavel; Pika, Tomas; Minarik, Jiri; Zapletalova, Jana; Bacovsky, Jaroslav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
BACKGROUND AND AIMS: Advances in the diagnosis and treatment of multiple myeloma (MM), place increasing demands on accurate stratification of patients as the starting point for optimal individualized therapy. The present study focused on assessing the association between HLC levels and the HLC-r to parameters of MM activity, prognosis and tumor mass volume.The objective was to assess the correlation of immunoglobulin (Ig), heavy/light chain (HLC) pairs (IgG-κ and-λ, IgA-κ and -λ HLC) and the ratio of monoclonal involved-HLC (i-HLC) to polyclonal uninvolved (u-HLC) Ig concentrations assessed by the Hevylite(TM) method with the free light chain κ/λ ratio (FLC-r), selected prognostic laboratory parameters i.e. Hb, platelets, albumin, β2-microglobulin (β2-M), Ca, lactate dehydrogenase (LDH), creatinine and the Durie-Salmon (D-S) and International Staging System (ISS), stages (1-3) for MM. METHODS: Hevylite assays were done on the sera of 132 MM patients at the time of diagnosis (IgG 94, IgA 38). HLC-r was calculated in the case of i-HLC-κ from the i-HLC-κ/u-HLC-λ ratio and for i-HLC-λ from the i-HLC-λ/u-HLC-κ ratio. D-S and ISS stages were evenly distributed. RESULTS: Md IgG-κ HLC-r was 64.8 (2.7-2222) and of IgG-λ HLC-r 49.6 (0.7-465.1), in the case of IgA-κ, Md HLC-r was 408.9 (3.4-3966) and for IgA-λ HLC-r the Md was 180.0 (0.1-3110). Normal levels of HLC pairs and HLC-r did not always rule out the diagnosis of MM. HLC-r correlated with FLC-r in IgG (r = 0.244, P = 0.018), but not in the IgA type. For IgG, HLC-r values were significantly different in patients with abnormal vs normal levels of Hb (P < 0.0001), albumin (P < 0.043), β2-M (P < 0.0001) and creatinine (P = 0.034) but not thrombocyte count, Ca or LDH. For the IgA isotype, we found a significant difference in HLC-r values only for thrombocyte count (P = 0.026) and β2-M (P = 0.016) but not for Hb, albumin, Ca, LDH or creatinine. For the IgG isotype there was a significant relationship of HLC-r index to stages 1-3 (P = 0.038) and substage A vs B (P = 0.048) according to D-S, and with high significance to stages 1-3 according to ISS (P = 0.005) and between stages 1 vs 3 (P = 0.001). For the IgA isotype, we found significant differences in HLC-r only between stages 1-3 (P = 0.025) according to D-S but not in the case of ISS. There were no significant correlations between i-HLC Ig levels and D-S or ISS stages in both IgG-κ and λ and IgA-κ and λ. Exceptions were significant differences for stages 1 vs 3 (P = 0.012) and 2 vs 3 (P = 0.017) for the IgG-λ isotype. There were no correlations of the HLC-r and u-HLC levels for either D-S or ISS stratifications in all HLC isotypes. CONCLUSION: We found a significant positive contribution of HLC-r using the i-HLC/u-HLC ratio even in the case of i-HLC-λ i.e. i-HLC-λ/u-HLC-κ. Variable results for the relationship of important laboratory parameters and D-S and ISS stratifications (stage 1-3) to HLC-r values in IgG and IgA isotypes make separate interpretation of the Hevylite method results necessary in clinical practice.
Keywords: heavy/light chain measurements; dospělí; Female; imunoglobulin G; Immunoglobulin Heavy Chains; Adult; imunoglobulin A; multiple myeloma; ženské pohlaví; lidé; Immunoglobulin A; mnohočetný myelom; Aged, 80 and over; těžké řetězce imunoglobulinů; Immunoglobulin G; prognóza; prognostic parameters; free light chain ratio; prospektivní studie; Male; Aged; Prospective Studies; heavy/light chain ratio; Prognosis; multiple myeloma stratification; lidé středního věku; senioři nad 80 let; Multiple Myeloma; senioři; mužské pohlaví; Middle Aged; Humans